Psychosocial Dynamics in Children's Decisions to Work: A Study of Self-Efficacy, Social Learning, and Reciprocal Determinism in Rural Areas of North Sumatra - Selian, Kiki Nur Halijah; Saragi, Muhammad Putra Dinata (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2025)
The phenomenon of child labor in rural areas such as Sei Musam, Langkat District, North Sumatra Province is often explained solely through an economic perspective, while the psychological and social dynamics of children remain largely unexplored. This study aims to uncover the socio-psychological factors shaping children's decisions to work at school age, emphasizing the importance of integrating children's internal perspectives and their social environment in understanding this phenomenon. Using a qualitative approach with a case study design, data were collected through semi-structured interviews with nine child workers and nine parents or supporting informants, and analyzed using thematic analysis techniques. The results of the study indicate that children's decisions to work are influenced by three main aspects of Bandura's social-cognitive theory: low self-efficacy in formal education, observational learning from the surrounding environment, and the reciprocal determinism mechanism between individuals, the environment, and behavior. Children are not only pressured by the school system but also motivated by a permissive social environment that normalizes child labor. Working becomes a means for them to build their identity, gain social recognition, and feel more psychologically empowered. These findings imply the need for social interventions that not only emphasize legal and economic dimensions but also consider children's motivations, perceptions, and social dynamics more comprehensively. This study makes an original contribution to the study of child labor by proposing a more comprehensive socio-psychological approach that focuses on children's subjective experiences, which have been largely overlooked in previous studies.